How did they come up with that expression for \(R_{icm}\)?
Here's what I came up with,
\(R_{icm} = \frac{v_{id}}{i_{b}}\)
\(i_{e} = \frac{v_{id}}{\frac{R_{E} + r_{e}}{2} + R_{EE}}\)
\(i_{e} = (\beta + 1)i_{b}\)
\(\Rightarrow R_{icm} = (\beta + 1)( \frac{R_{E} + r_{e}}{2} + R_{EE})\)
Am I doing this incorrectly?
Here's what I came up with,
\(R_{icm} = \frac{v_{id}}{i_{b}}\)
\(i_{e} = \frac{v_{id}}{\frac{R_{E} + r_{e}}{2} + R_{EE}}\)
\(i_{e} = (\beta + 1)i_{b}\)
\(\Rightarrow R_{icm} = (\beta + 1)( \frac{R_{E} + r_{e}}{2} + R_{EE})\)
Am I doing this incorrectly?
Attachments

54.1 KB Views: 19